2014
DOI: 10.1002/humu.22699
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Fragile X Syndrome Specific Molecular Markers in Human Fibroblasts: A Useful Model to Test the Efficacy of Therapeutic Drugs

Abstract: Fragile X Syndrome (FXS) is the most frequent cause of inherited intellectual disability and autism. It is caused by the absence of the fragile X mental retardation 1 (FMR1) gene product, FMRP, an RNA-binding protein involved in the regulation of translation of a subset of brain mRNAs. In Fmr1 knockout (KO) mice, the absence of FMRP results in elevated protein synthesis in the brain as well as increased signaling of many translational regulators. Whether protein synthesis is also dysregulated in FXS patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(65 citation statements)
references
References 52 publications
4
61
0
Order By: Relevance
“…Consistent with this role are numerous reports of excess mRNA translation and protein synthesis in animal models of FXS and cells from humans with FXS [61][62][63][64][65][66]. Recent studies suggest that FMRP-mediated repression involves its association with polyribosomes and ribosome stalling or direct interaction with the 80S ribosomal subunit [39,67,68].…”
Section: Mechanisms Of Fmrp-mediated Regulation Of Mrna Translation Imentioning
confidence: 65%
See 3 more Smart Citations
“…Consistent with this role are numerous reports of excess mRNA translation and protein synthesis in animal models of FXS and cells from humans with FXS [61][62][63][64][65][66]. Recent studies suggest that FMRP-mediated repression involves its association with polyribosomes and ribosome stalling or direct interaction with the 80S ribosomal subunit [39,67,68].…”
Section: Mechanisms Of Fmrp-mediated Regulation Of Mrna Translation Imentioning
confidence: 65%
“…Thus, these molecular defects may serve as biomarkers to evaluate the efficiency of disease-targeting therapies in humans. Potential biomarkers for FXS include altered signaling activity of extracellular signal-regulated kinase (ERK)1/2 and phosphoinositide-3-kinase (PI3K) [64][65][66][186][187][188], or altered protein expression or activity of FMRP targets [e.g., amyloid-β precursor protein (AβPP) or matrix metalloproteinase 9 (MMP-9) [162,189]]. Not all defects in signaling in the mouse model have been reproducible across laboratories.…”
Section: Molecular Defects As Potential Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently Matic et al (2014), showed a global downregulation of the MAPK/ERK pathway and decrease in phosphorylation level of ERK1/2 in the murine Fmr1 KO. However, others show an increase in this system in patient fibroblasts (68). A differential expression of many proteins involved in the p53 pathway, Wnt and calcium signaling was also found and led to postulate that calcium imbalance is part of pathophysiology of FXS (69).…”
Section: Neurobiologymentioning
confidence: 99%